2012
DOI: 10.5301/hip.2012.10350
|View full text |Cite
|
Sign up to set email alerts
|

Metal-On-Metal Hip Resurfacing in Patients Aged 65 Or Older

Abstract: There is little information regarding the clinical performance of hip resurfacing arthroplasty (HRA) in older patients. Eighty-seven patients (99 hips) aged 65 years or older received HRA while a control group of 52 patients (64 hips) received a primary THA. The average age was 69.2 years for the HRA group and 71.9 years for the THA group. Follow-up ranged from 2 to 13 years. UCLA walking, function and activity scores and SF-12 scores were higher in the HRA group. At 10 years, the Kaplan-Meier overall survivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
5
8
1
Order By: Relevance
“…Findings demonstrate good survival and functional outcomes with the BHR in both male and female patients ≥65 at up to ten years of follow up. Overall ten year BHR survival was 96.4 %, which is comparable with that reported in a smaller designer-surgeon series (96.7 %) using a different hip resurfacing implant in elderly patients (Table 3) [21]. In addition, the ten year survival for men (98.9 %) and women (91.9 %) was not significantly different, with survival for both genders within acceptable limits recommended by the National Institute for Health and Clinical Excellence (NICE) (revision rate ≤10 % at ten years for continued use of an implant) [33].…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Findings demonstrate good survival and functional outcomes with the BHR in both male and female patients ≥65 at up to ten years of follow up. Overall ten year BHR survival was 96.4 %, which is comparable with that reported in a smaller designer-surgeon series (96.7 %) using a different hip resurfacing implant in elderly patients (Table 3) [21]. In addition, the ten year survival for men (98.9 %) and women (91.9 %) was not significantly different, with survival for both genders within acceptable limits recommended by the National Institute for Health and Clinical Excellence (NICE) (revision rate ≤10 % at ten years for continued use of an implant) [33].…”
Section: Discussionsupporting
confidence: 77%
“…Findings presented here support this observation, with an OHS (median 4.4 %) similar to that in patients up to 50 years of age undergoing BHR by the same surgeon (median OHS 4.2 %) [36]. A recent nonmatched study of patients undergoing hip resurfacing and THR demonstrated significantly better postoperative pain, function and activity scores in the resurfacing group [21]. Although there was no matched patient group undergoing THR for this study, the functional outcome in elderly BHR patients (median OHS 4.4 %) represents a clinically significant difference compared with our institution's historic results following THR (median OHS 20.8 %) [24].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations